State estimator for microgrids - Peng, Xiao Yang. (2010)
State estimation provides a continuously real-time data of the whole observable power system. A complete state estimation includes the following parts: topology process, observability analysis, bad data detection and identification, state estimation solution and results. A traditional state estimator (SE) used at Power System Control Center (PSCC) usually does not have Phase Measurement Units (PMUs). As a consequence, without the measurements of phase angles, the results would not be accurate enough. In this project, PMUs were used in the Weighted Least Square (WLS) state estimation, and bad data detection and identification were discussed and enhanced. And then, an experiment on real network model would be carried out to test the SE. With the measurements of phasor angles, the accuracy of SE would be improved. Using bad data detection and identification, the result of the state estimation would be more reliable. In this project, the Chi-square χ2 bad data detection method and Hypothesis Testing Identification (HTI) method were used. The results of this project contributed to the implementation of PMUs, bad data processing in SE and the realization of the SE which was proposed in this project.